Linkage relationships between beta- and delta-structural loci and African forms of beta thalassaemia. - Weatherall, D J (1976)
Five families are described in which there have been matings between individuals doubly heterozygous for beta thalassaemia and the delta-chain variant haemoglobin A2' to normal persons. In all there were 24 informative offspring. There were no crossovers between the beta-thalassaemia and delta-chain loci; in three of the families the genes were linked in cis and in two families the genes were found in trans. Together with previously reported families there have now been 58 opportunities for crossing over between the beta-thalassaemia and delta-chain loci and there have been two possible and one highly probable crossovers. Of the total of 9 families reported to date 4 have had the genes for beta thalassaemia and Hb A2' in cis and 5 in trans. These findings are contrasted with the findings in families where a beta-chain structural variant and Hb A2' have been observed together and these genes have always been found in trans and never in cis. The reasons for linkage disequilibrium of this type are discussed. It is concluded tentatively that the distance between the delta-structural and beta-thalassaemia loci is greater than that between the delta-structural and beta-structural loci. To date this conclusion can only be applied to the beta+ -thalassaemia and beta-thalassaemia genes as found in the African population, since this is the only population with a high incidence of delta-chain mutants which allow linkage analysis of this type to be carried out.